RASUL SAW CLOSED DA'WAH: BUILDING ISLAMIC EDUCATION IN MAKKAH - Syuhada Irmadanti; Ellya Roza (JEICI - Journal of Education and Islamic Contemporary Issue, 2025)
This study examines the strategy of secret da’wah (as-sirriyyah) conducted by the Prophet Muhammad (peace be upon him) during the early period of his prophethood in Makkah and its contribution to the foundation of Islamic education. In a social context marked by oppression and threats from the Quraysh, the secret approach was chosen as a strategic step to protect the early Muslim community while deeply instilling the values of monotheism (tawhid) and morality. This research employs a qualitative library research method, analyzing relevant scholarly literature from books and accredited national and international journals. The findings reveal that the house of Al-Arqam ibn Abi Al-Arqam served as the first informal Islamic educational institution, functioning as a center for learning, faith strengthening, and character building among the Prophet’s companions. The learning materials focused on aqidah (creed), basic worship practices, moral development, and social solidarity, delivered through methods such as talaqqi (direct instruction), halaqah (study circles), and the Prophet’s exemplary conduct. The secret da’wah not only established the spiritual foundation of the early Muslim community but also created a holistic educational model that integrated cognitive, affective, and psychomotor aspects. The educational values applied during this period remain relevant to modern Islamic education, particularly in shaping a generation that is faithful, moral, and spiritually resilient in facing contemporary challenges.